ФИКЦИОНАЛНИОТ НАСПРЕМА ИСТОРИСКИОТ КРАЛЕ МАРКО ВО ИЗБОР БАЛКАНСКИ ЕПСКИ ПЕСНИ - Dimovska, Kristina (Philological Studies, 2019)
The paper makes an attempt to present the discrepancy theorists and folklore researchers often point out when they write about (the historical and ‘literary’, epic) figure of Krale Marko / Prince Marko. This can be achieved through comparative analysis of common motives that treat the battle of the epic hero with his opponents, in broad(er) Balkan context (with examples taken from Macedonian, Serbian, Bulgarian and Croatian epic songs). According to Tvrdko Čubelić and Kiril Penushliski, only certain social events were creatively transformed in epic motives and this is also applied for historical figures (such as Musa Kesedzija, Bele from Kastoria) which, as the figure of Krale Marko himself, bear only provisional similarities to their historical prototypes. The paper is based on the representation of Krale Marko as an epic hero in the different Balkan literary cultures and histories, thus marking his importance as a shared figure of memory.